NEGATIVE SOCIAL MEDIA CONTENT REPRESENTING PUBLIC PERCEPTIONS OF THE IMPLEMENTATION OF THE FREE NUTRITIOUS MEALS PROGRAM AND ITS IMPACT ON PUBLIC POLICY GOVERNANCE - K.P. Suharyono S. Hadiningrat; Teguh Yuwono; Febri Pramudya Wardani Febri; Verry A.J.M. Silalahi (Yayasan Inspirasi Merah Putih Indonesia, 2026)
Public criticism of the implementation of Indonesia’s Free Nutritious Meals program (Makan Bergizi Gratis, MBG), launched by President Prabowo Subianto on 6 January 2025, constitutes a form of social criticism in a democratic era. Social media content initially expressed positive attitudes and strong support for the program. As implementation progressed, however, a gap emerged between public expectations and conditions in the field. Repeated problems, including unexpected mass food-poisoning incidents, contributed to increasingly negative perceptions and created implications for public policy governance. This study used a descriptive qualitative design, a thematic narrative approach, and content analysis. Data were collected through observation and digital documentation of media that published negative or critical content about MBG during 2025. The study finds that negative online discussion was dominated by food safety and poisoning cases (55 percent) and criticism of budgeting and transparency (45 percent). The highest food-poisoning-related complaints were associated with West Java, the Special Capital Region of Jakarta, Central Java, and East Java, while budget constraints were most strongly discussed in frontier, outermost, and disadvantaged regions, particularly Papua, East Nusa Tenggara, and Maluku. The source document also cites an alleged corruption risk of IDR 49.5 billion reported by Indonesia Corruption Watch. The study recommends a National Nutrition Law, fundamental reform of the National Nutrition Agency, compliance with recommendations from other oversight institutions, constructive responses to public criticism, and regular internal and external monitoring and evaluation.